Determinan Etika Atas Penggelapan Pajak (Tax Evasion) : Persepsi Mahasiswa Akuntansi - Sabila Nurul Faidah; Mujiyati Mujiyati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The aim of this research is to identify the determinants of ethics in tax evasion. The population studied comprises students of Muhammadiyah University of Surakarta. The sample was determined using purposive sampling technique, which involves selecting samples based on specific criteria. Data processing was conducted using Statistical Package For The Social Sciences (SPSS) version 21 software. The analysis reveals that the variables of fairness and tax system significantly influence ethics in tax evasion, as evidenced by the significance of the fairness variable being lower than 0.05 and the positive influence indicated by the significance of the tax system variable. However, variables such as discrimination, quality of tax service, likelihood of detection of fraud, and love of money do not significantly affect ethics in tax evasion, as their significance values exceed 0.05.